"Where is the gang from the old days when we screwed Rina in the sycamore garden": An Image of the First Hebrew City in the Neighbourhood-plays of Hanoch Levin - Yavin, Omri (MiKAN, 2006)
This article examines the relationship between space as representedin Hanoch Levin’s neighbourhood plays and the actual spaceidentified with Tel Aviv. It shows that the familiar Tel-Aviv issubjected, by Levin, to a fictional-heterotopic landscape portrayedby the use of three major strategies. First, Levin dissociates Tel Avivfrom both its actual surroundings and its Israeli (geographical)context and juxtaposes it with the outside (mostly European andAmerican) world. Second, he superimposes the neighbourhoodspace onto the overall municipal space of the city, therebyforming a new space, that of a "city-neighbourhood". He thuschallenges the natural relationships between the city itself and theneighbourhood contained within it. Finally, Levin introduces intothis "city-neighbourhood" space an additional space that can beidentified with the Jewish-European shtetl. Through a strategy ofinterpolation, he inlays the first Hebrew city with elements of the)ewish core space, that of the Diaspora. Levin thus presents thecity of Tel Aviv as a global city, a city-neighbourhood, and an EastEuropean island within the Mediterranean Sea.